High-altitude hypoxia exacerbates dextran sulfate sodium (DSS)-induced colitis by upregulating Th1 and Th17 lymphocytes. Issue 1 (1st January 2021) - Gamah, Mohammed; Alahdal, Murad; Zhang, Yu; Zhou, Yiling; Ji, Qiaorong; Yuan, Zhouyang; Han, Ying; Shen, Xiangqun; Ren, Yanming; Zhang, Wei
ABSTRACT: High altitude hypoxia (HAH) involves the pathogenesis of ulcerative colitis (UC) and gastrointestinal erosions. However, the mechanism of effects of HAH in colitis remains controversial. This study reports the immunomodulation mediated by HAH to enhancing the severity of UC in the mice model. BALB/c mice were used to establish the UC model by dextran sulfate sodium (DSS) compared to wild type mice. Mice groups were exposed to hypoxic conditions in a hypobaric chamber with an altitude of 5000 m for 7 days. Then, Spleen, mesenteric lymph nodes and colon tissues were collected. The activity of UC, the infiltration of the immune cells, and the released cytokines were investigated. Results showed that the severity of DSS-induced UC significantly increased in mice exposed to HAH. The analysis of pathological changes showed increased weight loss and decreased colon length accompanied by diarrhea and bloody feces in the hypobaric hypoxia group. Interestingly, the levels of inflammatory cytokines IL-17, TNF-α, and IFN-γ in the spleen and mesenteric lymph node showed a significant increase within the colon of the hypobaric hypoxia group. The population of Th 1 and Th 17 cells in the spleen was significantly increased in mice exposed to hypobaric hypoxia compared NC group. Suggesting that high altitude hypoxia enhances colitis in mice through activating the increase of inflammatory Th1 and Th17 lymphocytes. In conclusion, this study revealed that hypobaric hypoxia directly increases the severity of UC in the mice model via increasing the activity of inflammatory CD4+ Th1 and Th 17 lymphocytes.